PENGARUH BRAND GESTALT DAN SELF-PLACE CONGRUITY TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI GEN Z DI MANADO BAY YANG DIMEDIASI VARIABEL NIAT BERKUNJUNG - Intan Enjilia Temo; Djurwati Soepeno; Christy Natalia Rondonuwu (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
The development of urban culinary destinations has intensified competition in attracting visitors, particularly among Generation Z, who tend to be critical and experience-oriented consumers. This study aims to analyze the influence of brand gestalt and self-place congruity on Generation Z’s revisit decisions at culinary destinations in Manado Bay, with visit intention acting as a mediating variable. This research employed a quantitative approach using a survey method targeting Generation Z visitors who had previously visited the area. Data were collected through questionnaires and analyzed using structural model analysis to examine the relationships among the research variables. The results indicate that brand gestalt and self-place congruity have a positive effect on visit intention. Furthermore, visit intention significantly influences revisit decisions. Visit intention also plays a mediating role in the relationship between brand gestalt and self-place congruity and revisit decisions. These findings suggest that a holistic perception of a destination and the congruence between visitors’ self-image and the destination image can enhance visitor loyalty.